Analisis Kontrastif Hubungan Kata Kerja Transitif dan Objek Dalam Bahasa Arab dan Bahasa Melayu - Kamarul Shukri Mat Teh (Universiti Sains Islam Malaysia, 2024)
Knowledge and experience in the first language are often used by students in learning foreign/second language. The differences and similarities of both native and target languages have resulted in positive and negative implications on learning a foreign/second language. This paper describes a contrastive analysis on the relationship between transitive verbs and objects in Arabic and Malay languages. The structure and element from the grammatical aspect in both languages have been studied. Contrastive analysis showed that there are several similarities such as the verbs for Arabic and Malay languages can be made transitive through the addition of prefixes and suffixes; transitive verbs that require two objects in Arabic and Malay languages need direct object and indirect object; and the object in the original active verb phrase is placed at the end of the sentence. Among the differences identified is that the transitivisation of verbs in the Arabic language usually involves adding prefixes or infixes whereas for the verbs in Malay language it only involves adding the prefixes, or prefixes and suffixes at same time; transitive verbs in the Arabic language could require three objects and this does not happen in Malay language; the i'rab address (flexi) in Arabic language plays an important role in differentiating objects from elements of other languages, while determining objects in Malay language is done through the meaning of lexicography and language style. Findings of the study led to pedagogical implications such as the need for sharing of analysis information with students, compilation of teaching materials, and updating teaching methods based on analysis outcomes.